2009
DOI: 10.1088/0022-3727/42/4/045408
|View full text |Cite
|
Sign up to set email alerts
|

Structural study of gallium oxynitrides prepared by ammonolysis of different oxide precursors

Abstract: A comparative structural study has been carried out on gallium oxynitride powders using XRD and Raman spectroscopy. Gallium oxynitrides have been prepared by ammonolysis of either NiGa2O4 ternary oxide or the citrate method-derived amorphous oxide. Their crystal chemistry is different and appears to be influenced by the nature of the oxide precursor: whereas gallium oxynitride obtained from amorphous gallium oxide crystallizes with the common wurtzite structure, gallium oxynitride obtained from NiGa2O4 crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Experimental and theoretical investigations on the ternary system Ga-O-N confirmed that no crystalline or amorphous oxynitride phases appear during these reactions [17]. Synthesis of GaON was successfully obtained by nitridation under NH 3 flow of other gallium precursors such as Ga(OH) 3 [7,12] or NiGa 2 O 4 [5,6]. Mn 2+ -and Li + -doped GaON were synthesized by nitridation of amorphous oxides obtained by the citrate route [8,9].…”
Section: Oxinitreto De Zinco E Gálio Foi Sintetizado Por Meio Da Nitrmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental and theoretical investigations on the ternary system Ga-O-N confirmed that no crystalline or amorphous oxynitride phases appear during these reactions [17]. Synthesis of GaON was successfully obtained by nitridation under NH 3 flow of other gallium precursors such as Ga(OH) 3 [7,12] or NiGa 2 O 4 [5,6]. Mn 2+ -and Li + -doped GaON were synthesized by nitridation of amorphous oxides obtained by the citrate route [8,9].…”
Section: Oxinitreto De Zinco E Gálio Foi Sintetizado Por Meio Da Nitrmentioning
confidence: 99%
“…Considering these results and those reported [6], we have chosen to index all of the reflections with a hexagonal würtizte-type structure according to the JCPDS file 032-0398. This card is related to a gallium oxynitride compound with a space group P6 3 mc and a = a 0 =3.186 Å and c = 3c 0 = 15.530 Å where a 0 and c 0 are the GaN parameters.…”
Section: [Figura 3: Padrão De Difração De Raios X Dos Pós Após a Nitrmentioning
confidence: 99%
See 1 more Smart Citation
“…Its crystal structure has been expected to be 6H polytypoid, because its Raman spectrum showed characteristics for both wurtzite (2H) and zinc-blende (3C) 16 . Such structural characteristics can be observed directly in single crystalline products.…”
mentioning
confidence: 99%
“…57) Our group has prepared wurtzite-type GaON with a chemical composition of (Ga 0.89 0.11 )(O 0.33 N 0.67 ) by ammonolysis of amorphous gallium oxide precursors obtained through the citrate route, 58) where the symbol indicates a gallium site vacancy. Some kinds of 3d transition metals were doped into the GaON to study the magnetic properties by using similar preparation methods.…”
Section: )41)mentioning
confidence: 99%